Electrocardiographic monitoring in severe falciparum malaria. - Bethell, D; Phuong, P; Phuong, C; Nosten, F; Waller, D; Davis, T; Day, N; Crawley, J; Brewster, D; Pukrittayakamee, S; White, N (1996)
Electrocardiographic monitoring over 24 h was performed with 53 patients with severe Plasmodium falciparum malaria (11 adults and 42 children) to assess the frequency of unrecognized cardiac arrhythmias. Nine patients (17%) died, 5 during the monitoring period and 4 afterwards. Pauses lasting 2-3 s were observed in 3 children, a single couplet in one, and a further child experienced frequent supraventricular ectopic beats which had not been detected clinically. In none of the patients who died could death be attributed to cardiac arrhythmia. Furthermore, no abnormality was detected which could have resulted from the often large doses of quinine, chloroquine or the artemisinin derivatives used for treatment. These results suggest that the heart is remarkably resilient even in the face of heavy parasite sequestration and other vital organ dysfunction, and that deaths from cardiac arrhythmias in severe malaria are rare. The need for routine cardiac monitoring of patients with severe and complicated P. falciparum malaria is questionable.